2010
DOI: 10.2174/156720510790274473
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimers Disease (AD) and Mild Cognitive Impairment (MCI) Patients are Characterized by Increased BDNF Serum Levels

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by cognitive decline with loss of memory. In the last years there has been a great interest on the early phases of AD, trying to identify the pathogenic mechanisms of AD and define early treatment modalities. In particular, Mild Cognitive Impairment (MCI) is attractive because it represents a transitional state between normal aging and dementia, although not all MCI patients automatically convert to AD. The neurotrophin brain-derived neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 32 publications
13
72
0
Order By: Relevance
“…Additionally, the sample included MCI patients and control, whereas only AD patients were used in the current study. Although the findings are contradictory to some previous findings on the relationship of BDNF to GDS scores, they are consistent with others showing an increase in BDNF early in Alzheimer's [16] and studies reporting an increase in BDNF in both MCI and Alzheimer's [17]. Our sample consisted of AD patients in the mild stage of dementia and this increased level of BDNF may be a compensatory upregulation to deal with the accumulation of Alzheimer's pathology.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, the sample included MCI patients and control, whereas only AD patients were used in the current study. Although the findings are contradictory to some previous findings on the relationship of BDNF to GDS scores, they are consistent with others showing an increase in BDNF early in Alzheimer's [16] and studies reporting an increase in BDNF in both MCI and Alzheimer's [17]. Our sample consisted of AD patients in the mild stage of dementia and this increased level of BDNF may be a compensatory upregulation to deal with the accumulation of Alzheimer's pathology.…”
Section: Discussionsupporting
confidence: 57%
“…As previously noted, there are mixed results in peripheral concentrations of BDNF, some indicating increases and others finding decreases associated with cognitive function [17, 18]. Postmortem brain, cerebrospinal fluid, and blood samples from patients with AD revealed lower BDNF levels than controls [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although neurotrophin brain-derived neurotrophic factor (BDNF) is suggested to support the survival of neurons and boost the growth and differentiation of new neurons and synapses, research yields mixed findings regarding peripheral assessments. One study found elevated peripheral levels of BDNF in AD and MCI [17], whereas another study found reduced peripheral levels of BDNF in AD, depending on the stage [18]. Meanwhile, there is a relative lack of knowledge relating peripheral neuroinflammation biomarkers and cognitive function specifically in patients with HF.…”
mentioning
confidence: 99%
“…Nevertheless, conflicting findings revealed no association or increased serum Bdnf levels in AD and MCI with respect to controls, suggesting that compensatory changes could also take place [5,6].…”
Section: Introductionmentioning
confidence: 96%